Evaluation of antibiotic usage in patient with fever in a private hospital in Yogyakarta (period January – June 2002) - Aris Widayati; L. Endang Budiarti; Imono Argo Donatus (Indonesian Journal of Pharmacy, 2004)
Fever as a symptom may indicate to any other diseases. According to the standard therapy by IDI (1998) fever should be treated without antibiotic, but the fact showed that 70 % antibiotics were used for treatment. This study aimed at describing about fever and evaluating antibiotic usage in patients with fever as a final diagnose by appropriateness, effectiveness, and safety as a criteria of evaluation.The present study was done with retrospective data collection and descriptive-evaluative design. Data was collected from medical records within a period from 2002 January to June. A number of 157 patients were used for the assesment.The highest percentage of patient’s fever was a group of 17 – 60 years old (63. 28%). The final diagnose was fever (29.58%) and others (70.42%) such as viral infection (17.16%), DHF (8.28%), DF (7.01%) and acute respiratory traction infection (5.92%). There were 29 kinds of antibiotics (79.62%) that given to the patients as an empirical therapy and the highest was pefloxacin (13.14%). The percentage of antibiotic usage in patients with fever as a final diagnose (50 patients) was 86.00% (21 kinds of antibiotics) and the highest was pefloxacin (17.19%). Both of fever less than 5 days ormore than 5 days were treated with antibiotic, which was inappropriate usage because fever less than 5 days related to viral infection. There was only 4.65% had a culture and sensitivity test, which was appropriate antibiotics usage. There were 46.51% no growth of culture and 48.84% without culture, which was inappropriate antibiotics usage. Treatment with and without antibiotics could normalize vital signs each was 90.70% and 85.71% with no significant difference (with non parametric exact probability Fisher analysis, CI 0.05) and RR value (95%, 0.69-1.30). Patient’s recoveries were 88.37% and 85.71% with and without antibiotic therapy with no significant difference (CI 95% and 0.96 RR value with CI 95%; 0.66 – 1.41). There were two cases (4.00%) of contraindication and 12.00% of potential drug interactions. According to the standard therapy and supporting data of this study, so that fever should not always be treated with antibiotic.Key words: antibiotic, fever, evaluation.